Higher Education Marketing Strategy Through 7P To Increase Public Interest (Case Study at STKIP PGRI Trenggalek) - Rukmini Ambarwati; Prim Masrokan; Agus Eko Sujianto (EDUTEC : Journal of Education And Technology, 2024)
This study aims to provide a comprehensive understanding of higher education marketing strategies through the 7P framework to increase public interest. A qualitative method with a phenomenological approach was employed, utilizing a case study design. Data collection methods included in-depth interviews, direct observation, and document analysis. The data were analyzed using triangulation to ensure the credibility of information from multiple sources. The research was conducted at STKIP PGRI Trenggalek. The results reveal that the 7P elements—product (a variety of services offered), price (more affordable compared to other institutions), place (strategic and accessible location), promotion (both internal and external efforts), people (qualified lecturers and staff), physical evidence (adequate facilities and infrastructure), and process (the lecture activities meet student needs)—play a significant role. A SWOT analysis was also performed to identify strengths, weaknesses, opportunities, and threats. The study suggests that by leveraging its strengths and opportunities, STKIP PGRI Trenggalek can mitigate weaknesses and avoid external threats. Continuous promotion and prioritization of service quality have enhanced the institution's image, contributing to a steady increase in public interest.